A clinical study of factors predicting prognosis in acute ischemic stroke in a tertiary care center in north Kerala - Kannan, Rijit; Alex, Anoop George; Sudeep, K. (International Journal of Research in Medical Sciences, 2017)
Background: Stroke is the second most common cause of death and third most common cause of disability in the world. Knowledge of prognostic factors is necessary for the clinician to make a reasonable prediction of outcome for individual patients, to provide rational approach to management and to help patients and their families understand course of the disease. Hence, this study to determine the prognostic factors in acute ischemic stroke with special emphasis on atrial fibrillation, hyperglycemia and fever was undertaken. Methods: This is a prospective and hospital based observational study of 70 patients with acute ischemic stroke. The diagnosis of acute ischemic stroke was based on history, physical examination and CT imaging. The severity was assessed based on Scandinavian Stroke Scale (SSS). The prognostic factors with special emphasis on atrial fibrillation, hyperglycemia and fever were studied based on the standard diagnostic criteria. Results: Prevalence of Atrial Fibrillation was 20% in present study. Mortality and dependency rates were significantly higher in AF group. Fever during the first few days of acute ischemic stroke was a statistically significant predictor of poor outcome. Neuronal damage in brain is directly proportional to its temperature. The results of the study confirm that hyperglycemia at stroke onset is an adverse prognostic factor with 33.33% mortality in hyperglycemic stroke. Conclusions: Atrial fibrillation, hyperglycemia and fever were found to be poor prognostic factors in acute ischemic stroke. Prompt recognition and correction of these poor prognostic factors improve the outcome for such patients.